Effects of Major Currency Realignment of Philippine Merchandise Trade - Bautista, Romeo M. (The Review of Economics and Statistics, 1977)
THE quantitative analysis of some economic effects of changes in exchange rates of the world's key currencies has been the subject of a few recent empirical studies,1 inspired presumably by the greater flexibility in currency exchange rates among developed countries that was initiated in the early part of this decade. Relatively large-scale equation systems are employed that take into account the simultaneous interaction among prices, incomes and spending in the economy usually divided into a number of developed countries and a Crest of the world category, the latter subsuming the less developed countries (LDCs). In the context of a small LDC, however, the complexity of the problem is somewhat reduced by the exogeneity of export and import prices (expressed in foreign currency) and the market concentration of LDC foreign trade typically in only a few developed countries. The Philippines is a case in point, about three-fourths of its trade flows throughout most of the post-war period being accounted for by Japan and the United States; moreover, certain principal trade commodities are dependent to a significant degree on only one or two dominant markets. Currency realignments involving these two countries, as exemplified by the 1971 Smithsonian Agreement, represent, therefore, a new form of external economic disturbance which may have significant repercussions on the country's balance of payments, output growth, income distribution and other policy objective variables. In this paper we attempt an evaluation of the direct effects on Philippine merchandise trade of the 1971 realignment of major currencies and the Central Bank decision to keep the exchange rate of the domestic currency (peso) fixed with respect to the U.S. dollar. First, a simplified framework of analysis is presented that identifies the parameters to be estimated for a quantitative assessment of the trade effects. We then estimate export supply and import demand functions for various trade commodities using annual data in the postwar period. The price coefficient estimates, together with the geographic distribution of Philippine trade flows in 1970, provide the empirical basis for examining the quantitative effects on Philippine merchandise trade of the altered sets of peso export and import prices attributable to the 1971 exchange rate changes.